Synthesis of Barbiturate Derivatives of D-Erythroascorbic Acid - Mukhlis, A-J.A.; Sarhan, B. M.; Rumez, R. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2016)
The   aim  of   this   work   is   the   synthesis  of   new   derivatives  of   barbiturate   of  D-erythroascorbic acid. To obtain these derivatives, the 5,6-O-isopropylidene-L-ascorbic acid (4) was chosen, which was prepared from the reaction of L-ascorbic acid (3) as a starting material with dry acetone in the presence of hydrogen chloride. The esterification of hydroxyl groups at C-2 and C-3 positions with excess of benzoyl chloride in dry pyridine was obtained compound (5). Hydrolysis for compound (5) in acetic acid (65%) gave the compound (6). Oxidation of the product (6) with sodium periodate results an Aldehyde (7), which was reacted with dimethyl malonate in the presence of potassium hydroxide to give the malonate (8). The cyclocondensation reaction for compound (8) with urea, thiourea and guanidine hydrochloride gave the following compounds (9), (10) and (11) respectively.      All these compounds were characterised by Thin Layer Chromatography (TLC) and FTIR spectra and some were characterised by (U.V-Vis) spectra, 1HNMR spectra and 13CNMR spectra.